Perception and Level of Knowledge About Menarche in Student of SMP Negeri 2 Tomohon - Angella P.Tangkulung; Theo W.E. Mautang; Deviana P.Munthe; Prycilia P.Mamuaja; Augustinus Butarbutar; Jilly Toar (CV. AFDIFAL MAJU BERKAH, 2026)
Adolescence is characterized by physiological, psychological, and social changes, one of which is menarche. The lack of knowledge makes some students experience confusion, anxiety, and embarrassment when experiencing it. This study aims to find out the perception and level of knowledge of SMP Negeri 2 Tomohon students about menarche. The type of analytical descriptive research with a cross sectional approach on 86 students in grades VII–VIII used a total sampling technique. Data were collected with questionnaires that had been tested for validity and reliability, then analyzed univariately. The results showed that the majority of respondents were 13 years old (61.6%) with the most menarche age of 11 years (57.0%). The main source of information comes from parents (82.9%). Most female students have a negative perception (57.0%), while the highest level of knowledge is in the sufficient category (72.1%).